Short communicationA unique case of systemic thromboembolism in a patient with arrhythmogenic right ventricular cardiomyopathy - Wozniak, Olgierd; Konka, Marek; Biernacka, Elzbieta K. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
We report a case of a 37-year-old woman with arrhythmogenic right ventricular cardiomyopathy (ARVC), after implantation of a cardioverter-defibrillator (ICD), who was admitted to our hospital because of focal infarctions in the right kidney and in the spleen. Echocardiography showed thrombi on the ICD electrode and the presence of patent foramen ovale. Patent foramen ovale was successfully closed by septal occluder. To our knowledge it is the first ever case report of paradoxical thromboembolism in a patient with ARVC.